Conserva??o in vitro DE Hyptis ramosa Pohl ex Benth. (LAMIACEAE) - Santos, Suzivany Almeida dos (2017)
The genus Hyptis is composed of about 400 species distributed throughout several countries, the majority being in a native and non-domesticated state. The genus has great importance for the pharmaceutical industry because of the high diversity found in its species. It has excellent pharmacological potential and is of great economic interest. Biological properties like it?s antimicrobial, anti - inflammatory, anesthetic, and insecticidal potential have already been demonstrated. However, in addition to the endemism present in many species, there are few works related to conservation of the genus and more research is needed to elucidate potential methods for its preservation. The objective of this research was the in vitro conservation of the species Hyptis ramosa. In addition to adjusting the protocols of cryopreservation of axillary guides and shoots, we aimed to contribute to the conservation of germplasm of this species. The microplants used came from the germination of seeds in MS1/2 medium. For the in vitro conservation, 10 treatments were evaluated, with different combinations between sucrose, mannitol, and sorbitol. After inoculation, the plants were maintained in a growth room for 240 days and evaluated at 60, 120, 180, and 240 days. Each evaluation quantified the number of shoots, shoot length, root number, and root length. For cryopreservation, the techniques of vitrification for axillary calluses and buds and for encapsulation of axillary shoots were evaluated. The tests were carried out in the Laboratory of Germination (LAGER) and Vegetable Tissue Culture (LCTV) of the Horto Florestal Experimental Unit da Universidade Estadual de Feira de Santana. With the results obtained, we concluded that in vitro conservation of microplants of this species is possible using the combination of 87.64 mM sucrose combined with 87.64 mM mannitol in MS medium (MURASHIGE; SKOOG, 1969). With the methodology used, cryopreservation of calluses and shoots of the species was not possible. Cell death occurred in the first stages of the callus vitrification process and in the cryogenic stage for the shoots.